The Importance of p-Doping for Quantum Dot Laser on Silicon Performance - Norman, Justin C.; Zhang, Zeyu; Jung, Daehwan; Shang, Chen; Kennedy, M. J.; Dumont, Mario; Herrick, Robert W.; Gossard, Arthur C.; Bowers, John E. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
p-type modulation doping of the quantum dot active region is known to improve high temperature and dynamic performance of quantum dot lasers. These improvements are critical to realizing commercially relevant quantum dot devices on silicon and are shown to enable continuous wave operation over 100 degrees C, nearly complete insensitivity to optical feedback, and orders of magnitude improvement in device reliability relative to unintentionally doped active regions. Also described is a spectrally resolved analysis of the effect of p-modulation doping on the optical gain revealing anomalous behavior that explains the high characteristic temperatures commonly observed in literature for similar devices on native substrate.
Keywords: AUGER RECOMBINATION; TEMPERATURE; SI